Relational Legacies Impacting on Veteran Transition From Military to Civilian Life: Trajectories of Acquisition, Loss, and Reformulation of a Sense of Belonging. (October 2019) - Albertson, Katherine
The veteran cohort has been inextricably linked in the general public's mind by media-generated perceptions of high risk and fear of crime, echoed in wider contemporary debates linking issues of place, social identity, social exclusion, and a loss of belonging in wider communities. Despite the growing interest in the longer term outcomes of transition from military to civilian life from policy-makers, practitioners, and academics, few qualitative studies explore the social and relational impacts of this transitional experience on those who have experienced it. Tensions and frustrations expressed by ex-forces personnel, engaging in addiction services with a history of engagement in the criminal justice sector, are explored through the lens of belongingness, loss and related citizenship frameworks to expose temporal impacts on the acquisition, loss, and reformulation of a sense of belonging across the life course. The relevance of a significant loss of belonging in the transition from military to civilian life is useful, given the widely accepted damaging consequences of having this need thwarted. This article concludes that a broader understanding of this largely disenfranchised grief can enable more informed reflexive opportunities to facilitate a valued military veteran citizenship status and thereby contribute to the formulation of current policy debates concerning the veteran question.